Pemberdayaan Masyarakat Desa Banguntapan Bantul Melalui Pembuatan Unit Usaha Tempe Kedelai - Andika Wisnujati; Linda Kusumastuti Wardana; Syamsul Ma’arif (Journal of Community Development, 2024)
Promoting the expansion of small and medium industries (IKM) is crucial for stimulating national economic development. Small and medium-sized enterprises (SMEs) operate in several industries and have a crucial role in augmenting the earnings of those with lower socioeconomic status. The importance of small and medium-sized enterprises (SMEs) in national economic development is highly significant, particularly during times of economic crisis. This was particularly obvious in Indonesia's recent economic downturn, where SMEs had greater resilience in confronting these problems compared to large corporations, which often experienced stagnation or even ceased operations. Science and technology are becoming increasingly crucial for the advancement of small firms, including the tempe sector. The small tempe sector has emerged as a significant element of the economy in numerous nations, exerting a crucial influence on stimulating economic growth at the regional level. Nevertheless, like to other industries of a smaller scale, the tempeh sector encounters several challenges, including issues pertaining to production effectiveness, product excellence, and environmental sustainability. By organizing community service activities, many programs have been established, such as promoting the significance of branding in product marketing, fostering innovation in product development, and offering guidance on calculating the Cost of Goods Production (HPP). The results indicate that the prospective partner has the capability to oversee an IKM business division focused on soybean tempeh under the TempeMU brand.